The Role of Learners' Psychological Well-Being and Academic Engagement on Their Grit - Huo, Jiaying (Frontiers in Psychology, 2022)
This review aimed at examining the related studies on the effect of English as a foreign language learners’ (EFL) psychological well-being and academic engagement as positive emotional constructs on learners’ grit. The positive significant effect of psychological well-being on learners’ grit has been confirmed in the literature review. Studies have shown that resilience, enjoyment, engagement, lack of depression, interest, and world meaningfulness can act as mediator variables in the relationship between psychological well-being and grit. Furthermore, few studies have been done on the effect of academic engagement on learners’ grit. The studies showed that some factors such as meticulousness, self-control, self-confidence, and motivation act as mediators in the relationship between academic engagement and grittiness. In the end, the pedagogical implications are expounded to promote the quality of language learning quality. This review also provides some suggestions for further research to clarify our perspective over positive emotional variables and their relationships with each other.